Nursing and Treatment Experience of COVID-19 with Facial Paralysis - Wang Yu BSN, RN; Yu Hai MD; Yang Xiaoli MSN, RN (SAGE Publishing, 2023)
Introduction Facial paralysis is one of the nervous system manifestations reported about COVID-19. There has been no consensus on the treatment and nursing care of COVID-19 combined with facial paralysis. On May 2022, a COVID-19 case with facial paralysis was reported to make suggestions on nursing care and treatment based on successful experience of curing the case with traditional Chinese medicine and western medicine. Case Presentation A 27-year-old male, was hospitalized because of "low fever for 12 days and difficulty in left side facial muscle movement for 2 days." The diagnosis of facial paralysis and COVID-19 infection (mild type）is definite which is based on the patient's medical history and test results afterwards. Management and Outcomes Medical staff made a comprehensive plan on COVID-19's basic nursing including nutritional support, vital signs monitoring and psychological evaluation, medication guidance including corticosteroids and traditional Chinese medicine, and specialized nursing procedures of facial paralysis. The symptoms of the patient were significantly improved after treatment with traditional Chinese medicine and low-dose corticosteroids. The COVID-19 nucleic acid test turned negative 12 days after admission, and the facial paralysis recovered 1 month later after discharge. Discussion Facial paralysis and COVID-19 can coexist. This study finds that COVID-19 (mild type） patients can be treated with traditional Chinese medicine instead of antiviral drugs. This paper puts forward reasonable suggestions that the nursing plan of patients with COVID-19 complicated with specialized diseases should be formulated together with specialist nurses. The nursing plan needs to be implemented on the "General + Specialized" mode.